Bioinspired Stable and Photoluminescent Assemblies for Power Generation. Issue 12 (1st February 2019) - Tao, Kai; Hu, Wen; Xue, Bin; Chovan, Drahomir; Brown, Noam; Shimon, Linda J. W.; Maraba, Oguzhan; Cao, Yi; Tofail, Syed A. M.; Thompson, Damien; Li, Junbai; Yang, Rusen; et al.
Abstract: Peptide assemblies are ideal components for eco‐friendly optoelectronic energy harvesting devices due to their intrinsic biocompatibility, ease of fabrication, and flexible functionalization. However, to date, their practical applications have been limited due to the difficulty in obtaining stable, high‐performance devices. Here, it is shown that the tryptophan‐based simplest peptide cyclo‐glycine‐tryptophan (cyclo‐GW) forms mechanically robust (elastic modulus up to 24.0 GPa) and thermally stable up to 370 °C monoclinic crystals, due to a supramolecular packing combining dense parallel β‐sheet hydrogen bonding and herringbone edge‐to‐face aromatic interactions. The directional and extensive driving forces further confer unique optical properties, including aggregation‐induced blue emission and unusual stable photoluminescence. Moreover, the crystals produce a high and sustained open‐circuit voltage (1.2 V) due to a high piezoelectric coefficient of 14.1 pC N −1 . These findings demonstrate the feasibility of utilizing self‐assembling peptides for fabrication of biointegrated microdevices that combine high structural stability, tailored optoelectronics, and significant energy harvesting properties. Abstract : Dense parallel β‐sheet hydrogen bonding and herringbone edge‐to‐face aromatic interactions endow cyclo‐glycine‐tryptophan crystals with unique mechanical robustness and ultrathermal stability, as well as steady visible photoluminescence. Moreover, these crystals produce ultrahigh piezoelectric coefficients. These findings demonstrate the feasibility of utilizing self‐assembling peptides for the fabrication of energy‐harvesting microdevices that combine high structural stability with tailored optoelectronics.